2014
DOI: 10.1037/h0099804
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parental divorce and alcohol abuse on adult offspring risk of lifetime suicide attempt in the united states.

Abstract: The influences of parental divorce and alcohol abuse on adult offspring lifetime suicide attempt have not been examined in national data. This study analyzed data from the 2001-2002 NESARC to estimate main and interaction effects of parental divorce and alcohol abuse on lifetime suicide attempt. Adjusted for controls, parental divorce and parental alcohol abuse independently increased odds of lifetime suicide attempt. The effect of parental divorce was not significantly moderated by parental alcohol abuse. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
(35 reference statements)
3
19
0
1
Order By: Relevance
“…The higher rates of psychiatric disorders among children living with parents who harmfully consume alcohol than their peers are consistent with the literature (Alonzo et al, ; Christoffersen & Soothill, ; Diaz et al, ; Ohannessian et al, ). Similarly, the higher number of life events, in particular negative and neutral ones, among children living with parents who harmfully consume alcohol than their peers is consistent with the literature (Anda et al, ; Dube et al, ; Floyd, Cranford, Daugherty, Fitzgerald, & Zucker, ; Hussong et al, ; Jacob & Windle, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The higher rates of psychiatric disorders among children living with parents who harmfully consume alcohol than their peers are consistent with the literature (Alonzo et al, ; Christoffersen & Soothill, ; Diaz et al, ; Ohannessian et al, ). Similarly, the higher number of life events, in particular negative and neutral ones, among children living with parents who harmfully consume alcohol than their peers is consistent with the literature (Anda et al, ; Dube et al, ; Floyd, Cranford, Daugherty, Fitzgerald, & Zucker, ; Hussong et al, ; Jacob & Windle, ).…”
Section: Discussionsupporting
confidence: 89%
“…Parental alcohol use disorders have been conceptualized as a chronic stressor that can lead to deleterious long‐term outcomes in children of parents who harmfully consume alcohol. Children of individuals with alcohol use disorder report higher rates of psychiatric disorders (Alonzo, Thompson, Stohl, & Hasin, ; Christoffersen & Soothill, ) and behavioural problems (Ohannessian et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Forty-five NESARC papers addressed childhood abuse, neglect and other adverse childhood experiences, finding relationships between childhood abuse or neglect and risk for adult disorders [66,289,291-294], even in older adults [295]. Childhood abuse or neglect also predicted chronic course of disorders [261,296-298].…”
Section: Major Findingsmentioning
confidence: 99%
“…Studies also showed harmful effects of harsh punishment and physical abuse [303-306]. Childhood stressors not involving direct maltreatment were also harmful, including parental loss [215-217], witnessing parental violence [307], and parental divorce [174,294,308-310]. Implications of this research are twofold: first, research on neurodevelopmental processes is needed to determine mechanisms of these effects; and second, public education is needed to inform parents about potential effects of common experiences (e.g., harsh physical punishment, divorce) on their children.…”
Section: Major Findingsmentioning
confidence: 99%
“…Adolescents who grow up with parents who are addicted to drugs and alcohol are more likely to turn to self-destructive behaviors such as suicide attempts (7, 8). Alonzo and colleagues (2014) studied the impact of parental addiction on children’s risk of suicide attempts in the United States and, after adjusting for sociodemographic and clinical variables such as age, gender, race, educational level, family income, and histories of depression, concluded that parental addiction nearly doubled the likelihood that children would attempt suicide in their lifetimes (9). Similarly, Fine and colleagues’ (2012) research in Pretoria (South Africa) on adolescents with a history of suicide attempts showed that 45% of these adolescents’ caregivers had a history of alcohol abuse and 14% had a history of drug abuse; thus, they reported that a history of alcohol and drug abuse among caregivers in an important predictor of adolescent suicide attempts (10).…”
Section: Introductionmentioning
confidence: 99%